Improving the ‘Reflective Writing’ part in the ‘portfolios of the practical-education students who are enrolled in Educ359 and Educ369 at Bethlehem University - Issa, Khalil Abdel Qader; Toubassi, Natalie Nabil (Journal of Educational and Psychological Sciences, 2018)
The aim of this research project is improving the ‘Reflective Writing’ part in the ‘portfolios of the practical-education students who are enrolled in Educ359 and Educ369 at Bethlehem University in the academic year. The present study employs Action research and utilized Gibbs’, 1988 to achieve this purpose.The sample of the research project were from the Educ359 and Educ369 students; total of 9 participants out of 17 that were included in the study, because they met the condition of submitting the portfolios of the aforementioned subjects; this condition was a requirement to fulfill the practical side of this research project. Additionally, the researchers designed observation and input cards to document the outcomes of the research.The results of this study demonstrated considerable improvement in the students’ levels in reflective writing in Educ369 in comparison with Educ359, despite thereduction of the number of paragraphs in the reflection parts in the former.The study recommends requiring reflective writing as part of or alongside one of the major courses in education the “Language and Thinking course Educ 251” . Moreover, the research project also recommends adopting Gibbs’ model in the reflective writing parts, and standardizing the practical education portfolios for all education majors at Bethlehem University.
Keywords: reflective writing; action research; practical education; experience file; Bethlehem University